Gambaran Work Engagement Pada Karyawan PT X (Perusahaan Manufaktur) Di Tangerang - Dhanisa Khaira; Reza Fahlevi; Debora Basaria (Psikologi Prima, 2024)
PT X is one of the largest companies in Indonesia engaged in manufacturing and is located in Tangerang. The development of PT X does not escape the role of its human resources in being able to continue to compete with other similar companies. For this reason, human resources are an asset for the Company and play an important role because they will affect the development and productivity of the organization. At PT X, some employees show that they enjoy their work, and some of them feel very proud and attached, but others look less excited when working. Work engagement is one of the things that influence it. Work engagement is defined as the extent to which employees psychologically feel bound and connected to their work. Work engagement is characterized by vigor, dedication, and absorption. This study uses quantitative methods to look at work engagement in employees at PT X. Participant data was obtained through the Utrecht Work Engagement Scales questionnaire consisting of 17 items (UWES-17). Participants in this study amounted to 106 employees at PT X aged 21-55 years. The results showed that PT X employees were classified as high (M = 4.83) and had high scores in each dimension, with the highest scores in the dimensions of dedication (M = 5.21), vigor (M = 4.84), and absorption (M = 4.43). These results show that some PT X employees have high work engagement. Thus, it can have a positive impact on the success of the Company.